STIMULASI PERILAKU KAWIN OWA JAWA (Hylobates moloch Audebert, 1798) JANTAN MENGGUNAKAN SANREGO (Lunasia amara Blanco) 300 MG - Dita Haristyaningrum; Burhanuddin Masy'ud; A Machmud Thohari (Department of Forest Resources Conservation and Ecotourism - IPB University, 2014)
Javan gibbon is endemic and endangered species in Java Island, because of that this species needs intensive conservation program. Javan Gibbon Center (JGC) has concern for conservation javan gibbon. The former research has identified that male javan gibbon in JGC not quite enough to response breeding behavior whose performed by female. Therefore, the research was conducted to stimulating on mating behaviour of male by using sanrego, as one of an aphrodisiac plant with 300 mg dose. Sanrego was give everyday throuhg oral and combined with food. The monitoring start at 06.30 until 16.30 with direct observation, and journalize the behavior in tally sheet between the javan gibbon couple, in particular the male gibbon. The result was show that sanrego was gived the effect to mating behavior of male gibbon, although not until on significant level. Keyword: Aphrodisiac, Javan gibbon, Javan gibbon center, Mating behavior, Sanrego (Lunasia amara).